Answer:
Simplify the radical by breaking the radicand up into a product of known factors, assuming positive real numbers.
Exact Form:√133
Decimal Form:
11.53256259…
Step-by-step explanation:
Answer:
(The solution is (4, -11).
Step-by-stp explanation:
Let f(x) = g(x) = y:
y = 3x − 23
y = -4.5x + 7 Subtract the second equation from the first to eliminate y:
0 = 7.5x - 30
7.5x = 30
x = 4
Plug this into the first equation:
y = 3(4) - 23
y = -11.
Answer:
The answer is : 2/3
Step-by-step explanation:
2+9x^2=6
9x^2 = 6 - 2
9x^2 = 4
x^2 = 4/9
x = √(4/9)
x = 2/3